Restoration of tendon repair microenvironment by grapefruit exosome-loaded microneedle system for tendinopathy therapy - Zhang, Yuan; Zhang, Ruiyang; Zhang, Ti; Mu, Yuhao; Juma, Talante; Li, Xu; Li, Hao; Guo, Quanyi; Cao, Yongping (Frontiers in Bioengineering and Biotechnology, 2025)
Tendinitis repair remains challenging due to the limited self-renewal capacity of tenocytes and persistent inflammatory microenvironment. Conventional therapies remain limited by systemic drug toxicity and fail to coordinate immunomodulation with matrix remodeling. Plant-derived extracellular vesicles have demonstrated tissue repair potential owing to their unique bioactive components and exceptional cross-species compatibility. Nevertheless, their therapeutic role in tendon matrix regeneration remains underexplored. Here, we developed a grapefruit-derived exosome-loaded microneedle patch (MN@GF-Exos) to synergistically restored tendon structure and functions. Grapefruit-derived exosomes (GF-Exos) were loaded into dissolvable hyaluronic acid microneedles (MNs) for sustained release. GF-Exos reversed oxidative stress in tenocytes, enhancing cellular proliferation and migration, restoring collagen I synthesis, and polarizing macrophages toward M2-repair phenotypes. Transcriptomics revealed GF-Exos modulated cytokine-cytokine receptor interactions, suppressing inflammation-related pathways and activating ECM organization genes. In collagenase-induced tendinopathy mice, MN@GF-Exos enhanced gait recovery and extracellular matrix remodeling. Histology confirmed reduced fibrosis without ectopic ossification. Systemic safety was validated by unchanged organ histology and within-normal-limits serum biomarkers. This dual-functional system leverages plant exosomes’ multi-component synergy and MN’s spatiotemporal control, offering a translatable strategy for chronic tendon regeneration.